PENGARUH PENEMPATAN KERJA DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN AGAM - Misharni; Ayu Ningsih (Jurnal Point Equilibrium Manajemen dan Akuntansi, 2020)
This study aims to determine the effect of work placement on employee job satisfaction, the effect of workload on employee job satisfaction, the effect of work placement and work load on employee job satisfaction. This research is using quantitative data, data collected through a questionnaire and if using SPSS version 16, with a total sample of 36 people. The results of the study can be concluded,work placement affects employee Job Satisfaction at Agam Regency Political Unity Agency, Workload does not affect Employee Job Satisfaction in Agam Regency National Unity and Politics Agenc, simultaneous Work Placement and Workload affects Employee Job Satisfaction at Agam Regency Political Unity Agency, with R Square 750 or its influence 75% while 25% is influenced by other than the model under study. Suggestions in this study are,it is hoped that the Agam Regency National Unity and Politics Board will place employees according to their expertise and experience,it is hoped that the Agam Regency National Unity and Politics Board will provide workloads in accordance with standard work portions and modest work volume, it is hoped that the Agam Regency National Unity and Politics Board will pay attention to employee job satisfaction, the leaders are expected to pay attention or provide compensation / rewards to employees according to the work volume of their employees.